Electrospraying: Possibilities and Challenges of Engineering Carriers for Biomedical Applications—A Mini Review - Wang, Jiamian; Jansen, John A.; Yang, Fang (Frontiers in Chemistry, 2019)
Electrospraying, a liquid atomization-based technique, has been used to produce and formulate micro/nanoparticular cargo-carriers for various biomedical applications, including drug delivery, biomedical imaging, implant coatings, and tissue engineering. In this mini-review, we begin with the main features of electrospraying methods to engineer carriers with various bioactive cargos, including genes, growth factors, and enzymes. In particular, this review focuses on the improvement of traditional electrospraying technology for the fabrication of carriers for living cells and providing a suitable condition for gene transformation. Subsequently, the major applications of the electrosprayed carriers in the biomedical field are highlighted. Finally, we finish with conclusions and future perspectives of electrospraying for high efficiency and safe production.